2021
DOI: 10.1080/2162402x.2021.1883890
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic profiling and prognostic significance of immune infiltrates in esophageal squamous cell carcinoma

Abstract: The tumor microenvironment (TME) of esophageal squamous cell carcinoma (ESCC) impacts tumor progression but is poorly understood. We obtained tumor tissues from 279 patients after esophagectomy and characterized the TME in intraepithelial and stromal regions using multiplex fluorescent immunohistochemistry (mfIHC). A heterogeneous immune population infiltrating tumor and the uninvolved esophageal tissue were observed. The infiltration of intraepithelial programmed death ligand 1 (PD-L1)positive tumor-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Though many studies of lung cancer have revealed the different effect of cigarette smoker and non-smoker about tumor microenvironment, how cigarette smoke alters ESCC immune infiltrating is largely unknown. In our previous study 18 , heterogeneous immune population infiltrating intraepithelial and stromal region, which was associated with overall survival, was observed. In this study, we further analyzed the effect of cigarette smoking on the immune cell infiltration of ESCC tissue samples.…”
Section: Introductionmentioning
confidence: 77%
“…Though many studies of lung cancer have revealed the different effect of cigarette smoker and non-smoker about tumor microenvironment, how cigarette smoke alters ESCC immune infiltrating is largely unknown. In our previous study 18 , heterogeneous immune population infiltrating intraepithelial and stromal region, which was associated with overall survival, was observed. In this study, we further analyzed the effect of cigarette smoking on the immune cell infiltration of ESCC tissue samples.…”
Section: Introductionmentioning
confidence: 77%
“…Intratumoural CD8+ T cell infiltration was increased in TLS‐mature ESCCs, which is a significant factor correlating with prolonged ESCC survival. 7 Whether TLS B cells or DCs cross‐present tumour antigens to CD8+ T cells or whether CD4+ Th cells are involved in the generation of CD8+ cytotoxic T cell responses inside or outside TLSs have not been settled. 10 As decreased expression of MHC I antigen presentation molecules was observed in mature TLSs compared to immature TLSs, we speculated that increased CD4+ Th cells, which were activated with Th17 signatures in mature TLSs, may take part in priming and enhancing CD8+ T cells outside TLSs in ESCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, allergy and cancer have different dendritic cell phenotypes, prevailing the activated DC in atopic subjects, while the antigen presentation by tolerizing DCs is induced in cancer environment preventing anti‐tumour T‐cell responses. The possibility to drive the activation of effector DCs can be a key to stimulate anti‐tumour immunity by the activation of cytotoxic CD8 + lymphocytes against tumour antigens 46 …”
Section: Role Of Immune Cells In Allergy and Cancermentioning
confidence: 99%
“…The possibility to drive the activation of effector DCs can be a key to stimulate anti‐tumour immunity by the activation of cytotoxic CD8 + lymphocytes against tumour antigens. 46 …”
Section: Role Of Immune Cells In Allergy and Cancermentioning
confidence: 99%